The role of Social media in enhancing intellectual security in Saudi society -Twitter as a model- An applied and analytical study for the Global Center for Combating Extremist Ideology (Etidal) - Alsowailem, Mohammad Ibrahim (Journal of Humanities & Social Sciences, 2024)
The study aimed to identify Social media in intellectual security in the Saudi society - a model study - across several social and cultural dimensions. From the The month of May year (2017) until the date (31/12/2021). The study concluded that the account of the Global Center for Combating Extremist Ideology (Etidal) presented subjects a scientific on the issues of the family institution, the educational institution, social institutions, the Islamic personality, moderation, the culture of dialogue, and belonging and citizenship, have been show a very rare and insufficient proposal to enhance intellectual security in Saudi society. And These subjects (issues of tolerance and coexistence, and rejecting violence and terrorism) Presented a lot on the account. Finally, the study concluded with a set of recommendations, including: the need to work on activating the account in preventive efforts and increasing the number of topics that would achieve intellectual security in Saudi society, which was found from the results of the study that the degree of the account’s contribution to the Twitter network was insufficient in it, work on rooting Sharia Islamic in messages addressed to users of the Twitter network and the use of mental and transferred from Islamic heritage evidence in support of topics that develop intellectual security.